Diana and Nubia, princesses of the Amazons - Hale, Shannon; Hale, Dean, 1972- (DC Comics, 2022)
Princess Nubia loves her mothers, their home on Themyscira, and all her Amazon aunties, but when Princess Diana is assigned to her bedroom she must learn to live and excel with her new sister.